A new species of Aphis (Hemiptera:Aphididae) in Missouri on St. John’s Wort, Hypericum kalmianum, and re-description of Aphis hyperici Monell - Lagos, Doris M.; Puttler, Benjamin; Voegtlin, David J.; Giordano, Rosanna (Zootaxa, 2012)
Aphis mizzou, n. sp. is described from specimens collected in Missouri, USA, on Hypericum kalmianum (Clusiaceae).Both apterous and alate viviparae are described and illustrated and a key is provided to apterae of the six species of Aphisthat feed on Hypericum. Neighbor-joining analysis of cytochrome oxidase (COI) and nuclear elongation factor (EF1-α)indicated a close relationship of the new species with Aphis hyperici but verified its distinctness, the pairwise sequencedivergence for COI between these two species being 3.2%. In addition, Aphis hyperici Monell is redescribed, including first descriptions of the fundatrix, ovipara and alate male of that species.